Experimental study of the particle agglomeration on its mechanical properties of collapsible loess - Zhao, Meng; Wu, Hong-Gang; Guo, Wei; Tan, Bo-Ren; Hu, Cheng; Deng, Rui; Chen, Li-Yi (Frontiers in Earth Science, 2022)
Loess is found all over the world, this soil exhibits behavior that is related to their fomation history , mineralogy,and microstructure, which can cause serious geotechnical engineering problems. This paper presents Baozhong railway is a key railway for guyuan city, in ningxia province of china. Which is an important city of the belt and road. Based on field investigations treasure middle section of the railway in the study area, the scene more serious diseases subgrade settlement, local roads embankment platform dislocation occurs, lots of cracks were founded, while the ballast roadbed sedimentation due elevate, increase the upper load subgrade , leading to more severe uneven settlement. Significant differential settlements were encountered . In order to analyze the causes of the railway line settlement, samples were collected from the collapsible loess subgrade , Consolidation test, particle size analysis test, XRD diffraction test, and scanning electron microscopy test were performed, and the the mechanism of the subgrade disease were studied. The results reveal that loess which collected from severe differential settlements at locations has a highly compressible, and their clay content and agglomeration level were generally low. These results illustrated that the particle size of 20-50 microns has a direct effect on its mechanical properties of loess. This part of the particles has a cementation effect, which can effectively connect the large particles of the skeleton to form particle agglomerates, which is an effective composition of loess clay minerals. Therefore, the loess structure was not stable due to its relatively low internal molecular attraction. When such saturated collapsible loess subgrade subjected to train vibration load, the soil might be liquefied and its structure might be instable. If the drainage of the subgrade was not well designed, severe differential settlements might occur. The research results are of great significance to the study of the relationship between loess particle composition, microstructure and its macromechanics.